Structural and functional characterisation of a novel peptide from the Australian sea anemone Actinia tenebrosa. (October 2019) - Elnahriry, Khaled A.; Wai, Dorothy C.C.; Krishnarjuna, Bankala; Badawy, Noha N.; Chittoor, Balasubramanyam; MacRaild, Christopher A.; Williams-Noonan, Billy J.; Surm, Joachim M.; Chalmers, David K.; Zhang, Alan H.; Peigneur, Steve; Mobli, Mehdi; et al.
Abstract: Sea anemone venoms have long been recognised as a rich source of peptides with interesting pharmacological and structural properties. Our recent transcriptomic studies of the Australian sea anemone Actinia tenebrosa have identified a novel 13-residue peptide, U-AITx-Ate1. U-AITx-Ate1 contains a single disulfide bridge and bears no significant homology to previously reported amino acid sequences of peptides from sea anemones or other species. We have produced U-AITx-Ate1 using solid-phase peptide synthesis, followed by oxidative folding and purification of the folded peptide using reversed-phase high-performance liquid chromatography. The solution structure of U-AITx-Ate1 was determined based on two-dimensional nuclear magnetic resonance spectroscopic data. Diffusion-ordered NMR spectroscopy revealed that U-AITx-Ate1 was monomeric in solution. Perturbations in the 1D 1 H NMR spectrum of U-AITx-Ate1 in the presence of dodecylphosphocholine micelles together with molecular dynamics simulations indicated an interaction of U-AITx-Ate1 with lipid membranes, although no binding was detected to 100% POPC and 80% POPC: 20% POPG lipid nanodiscs by isothermal titration calorimetry. Functional assays were performed to explore the biological activity profile of U-AITx-Ate1. U-AITx-Ate1 showed no activity in voltage-clamp electrophysiology assays and no change in behaviour and mortality rates in crustacea. Moderate cytotoxic activity was observed against two breast cancer cell lines. Graphical abstract: Image 1 Highlights: The 13-residue peptide UAITx-Ate1 was identified in the transcriptome of the sea anemone Actinia tenebrosa. The transcript abundance was high in tentacles but low in acrorhagi and mesenteric filaments. The three-dimensional structure of UAITx-Ate1 consists of an extended loop structure with no helices or β-sheets. U-AITx-Ate1 has weak affinity for biological membranes. Moderate cytotoxic activity was observed against breast cancer cell lines.